Penerapan sosiodrama untuk meningkatkan kemampuan resolusi konflik pada komunitas anak jalanan kendari - Ishlah Hakim (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The research is amimed to know whether or not the application of sociodrama is abe to enhance conflict resolution skill towards the street children community in Kendari. This reserch was quantitaitve research using experimental approach. The experimental research design used is pre-experimental design in the form of one group pre-test-posterst design. The data collection used is scale, observation, and FGD (Focus Group Discussion) . The population in the research is 42 people. The sample in the research consisted of 12 people. The sampling in the research used is nonprobskill sampling with sampling purposive technique. The data of the research was analyzed quantitatively using Wilcoxon signed ranks test. The findings shows that sociodrama was able to enhance the conflict resolution skill towards the street children community in Kendari.